Self-assessment of general health status in patients with five common shoulder conditions - (:unkn) unknown (MOSBY-YEAR BOOK INC, 1998)
The SF-36 Health Survey is a patient self-administered general health status evaluation designed to measure the impact of disease on an individual's perception of his or her health. Five hundred forty-four patients with five common shoulder conditions (anterior glenohumeral instability (149 patients), complete reparable rotator cuff tear (1 1 1 patients), adhesive capsulitis (100 patients), glenohumeral osteoarthritis (67 patients), and impingement (1 1 7 patients)) completed the SF-36 Health Survey before undergoing treatment. When compared with U.S. general population norms, the patients with each of these shoulder conditions had statistically significant decreases in their health for Physical Functioning, Role-Physical, Bodily Pain, Social Functioning, Role-Emotional, and the Physical Component Summary as measured by the SF-36 Health Survey. Comparison with published data demonstrated that these shoulder conditions rank in severity (in terms of affecting a patient's perception of his or her general health) with Five major medical conditions hypertension, congestive heart failure, acute myocardial infarction, diabetes mellitus, and clinical depression). The data presented in this study should serve as a baseline to document the impact of shoulder musculoskeletal conditions and possibly to allow comparison among various methods of operative and nonoperative treatment.
Keywords: STATUS INSTRUMENTS